2020
DOI: 10.3390/pathogens9010051
|View full text |Cite
|
Sign up to set email alerts
|

HMPV in Immunocompromised Patients: Frequency and Severity in Pediatric Oncology Patients

Abstract: Cancer is the first cause of death by disease in childhood globally. The most frequent types of cancers in children and adolescents are leukemias, followed by brain and central nervous system tumors and lymphomas. The recovery rate of cancer in children is around 80% in developed countries and up to 30% in developing countries. Some of the main causes of complications in children and adolescents with cancer are respiratory viral infections, mainly in bone marrow-transplanted patients. Respiratory viruses have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Human metapneumovirus is a major cause of infection in children worldwide [37]. Since it was discovered, several international studies have highlighted how primary infection occurs before 5 years of age and that all children are potentially infected at 10 years of life.…”
Section: Human Metapneumovirus (Hmpv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Human metapneumovirus is a major cause of infection in children worldwide [37]. Since it was discovered, several international studies have highlighted how primary infection occurs before 5 years of age and that all children are potentially infected at 10 years of life.…”
Section: Human Metapneumovirus (Hmpv)mentioning
confidence: 99%
“…Another more recent review highlighted that 7% of all children with cancer who developed a respiratory infection were positive for hMPV. Of this 7%, about 1% died; 2.3% of pediatric patients who received a transplant and were hMPV positive died as well [37].…”
Section: Human Metapneumovirus (Hmpv)mentioning
confidence: 99%
“…Mortality rates at 100 days in some studies have been high (reported as high as 43%), and mortality has been associated with steroid therapy, oxygen requirement >2 L, or mechanical ventilation, and bone marrow as stem cell source [137]. Reports also suggest higher attack rates in pediatric and adolescent HSCT populations [138].…”
Section: Human Metapneumovirusmentioning
confidence: 99%
“…Children younger than 6 months of age are about three times more likely to be hospitalized because of hMPV infection than children from 6 months to 5 years [ 6 ]. Other susceptible populations include children with underlying high-risk conditions [ 6 ], the elderly [ 7 ], and immunocompromised individuals [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%